KREATIVITAS SARI APRILIANTI DALAM KARYA TARI CAHAYA PIRDI DI SANGGAR SENI NUSA KIRANA KOTA PALEMBANG - Wardani, Suci Kesuma; Slamet, Slamet (Greget : Jurnal Kreativitas dan Studi Tari, 2023)
The research entitled Sari Aprilianti's Creativity in the Cahaya Pirdi Dance Work at the Nusa Kirana Art Studio in Palembang City contains the Cahaya Pirdi dance which is a composition of the Pirdi dance by Sari Aprilianti in 2016. The Cahaya Pirdi dance is a new creative dance work that illustrates that humans must strive to achieve something for the sake of survival on earth. At the beginning of the composition, this dance was specifically for children, but in 2020 the Cahaya Pirdi dance was danced for the first time by teenagers to take part in a competition. The problems formulated in this study are the first, what is the form of the Cahaya Pirdi dance, and the second is how is Sari Apriliani's creativity in creating the Cahaya Pirdi dance. Answering the problem about the form of the Cahaya Pirdi dance, Soedarsono's theory of form is used that the form of dance includes interrelated elements including dance movements, floor patterns, dance music, make-up and costumes, properties, time and place of performance. Meanwhile, to answer the problem about Sari Apriliani's creativity, the theory from Rodhes' theory known as 4P (Four P's Creativity) developed by Utami Munandar states that creativity usually has four dimensions, namely personal, process, product, and driver. Based on the object to be studied, the study uses a descriptive analysis method. The results of the study show that Sari Apriliani's creativity is influenced by internal factors, such as her life experiences and artistic vision, and external factors, such as the cultural environment and social support. In addition, this study discusses various supporting elements of the work, such as music, costumes, and stage design. All of these components play an important role in creating an aesthetic experience for the audience